A Comparative Analysis of Poststructuralist Thought and Critical Pedagogy - Shahbazi , Sirous; Khatirpasha, Kiumars; Zameni, Farshideh (Assessment and Practice in Educational Sciences, 2025)
This study aims to comparatively analyze poststructuralist thought and critical pedagogy across their ontological, epistemological, anthropological, and axiological dimensions to identify intersections and divergences that inform contemporary educational theory and practice. The research employed a qualitative meta-synthesis design, integrating systematic review and thematic analysis to synthesize theoretical and empirical literature published between 2003 and 2025. Using a PRISMA-guided protocol, relevant studies were selected from international and regional databases through purposive sampling, emphasizing works focused on poststructuralist and critical pedagogical frameworks. Each study was coded and analyzed to extract philosophical dimensions and conceptual categories. The meta-synthesis process incorporated interpretive comparisons of discursive, ideological, and pedagogical structures, while thematic analysis was applied to refine core patterns of convergence and divergence between the two paradigms. The results indicate that both poststructuralism and critical pedagogy reject essentialism, absolute truth, and positivist epistemology, emphasizing the social construction of knowledge and reality. Poststructuralism privileges linguistic discourse, deconstruction, and the contingency of meaning, while critical pedagogy centers on praxis, empowerment, and social transformation. Despite these differences, both share commitments to reflexivity, plurality, and critique of power. Their epistemological alignment underscores knowledge as relational and political, while their ontological perspectives affirm the dynamic and historical constitution of reality. Anthropologically, poststructuralism emphasizes decentered subjectivity, whereas critical pedagogy upholds agency and consciousness. Axiologically, both challenge moral absolutism, yet critical pedagogy reorients relativism toward justice, equality, and liberation. Integrating poststructuralist critique with critical pedagogy’s emancipatory orientation creates a dialectical framework that unites deconstruction with ethical reconstruction. This synthesis enables education to function simultaneously as a site of critical inquiry and social transformation, promoting pluralism, reflexivity, and democratic engagement.